Settling the French Historical Past: The Example of Lankhor Games - Jankowski, Filip (Replay. The Polish Journal of Game Studies, 2019)
The aim of the article is to illustrate how the historical past of France could be revised in digital games. Two Lankhor games (Le Manoir de Mortevielle and Maupiti Island) were used for research purposes, analyzed using the social-semiotic analytical model of Óliver Pérez-Latorre, Mercè Oliva and Reinald Besalú. The results of the research allow us to find in both games references to French collaboration with Germans within the Vichy (Mortevielle), as well as to genocidal colonial practices against the so-called natives (Maupiti Island).